Assessing physical activity and function in patients with chronic kidney disease: a narrative review - Bakker, Esmée A (Clin Kidney J, 2020)
Physical activity potentially improves health outcomes in patients with chronic kidney disease (CKD) and recipients of kidney transplants. Although studies have demonstrated the beneficial effects of physical activity and exercise for primary and secondary prevention of non-communicable diseases, evidence for kidney patients is limited. To enlarge this evidence, valid assessment of physical activity and exercise is essential. Furthermore, CKD is associated with a decline in physical function, which may result in severe disabilities and dependencies. Assessment of physical function may help clinicians to monitor disease progression and frailty in patients receiving dialysis. The attention on physical function and physical activity has grown and new devices have been developed and (commercially) launched on the market. Therefore the aims of this review were to summarize different measures of physical function and physical activity, provide an update on measurement instruments and discuss options for easy-to-use measurement instruments for day-to-day use by CKD patients. This review demonstrates that large variation exists in the different strategies to assess physical function and activity in clinical practice and research settings. To choose the best available method, accuracy, content, preferable outcome, necessary expertise, resources and time are important issues to consider.